Bestia. (Gdynia : [s.n.], 1946)
Afisz inf. o seansach filmu w gdyńskim Domu Marynarza w sierpniu 1946 r.
Keywords: Kino polskie -- 1945-1960 -- druki ulotne; Kina -- Polska -- Gdynia -- 1945-1970 -- druki ulotne; Gdynia (Polska) -- 1945-1970 -- druki ulotne